Evaluation of Preventive Operational Control in Maintaining Treated Water Turbidity Stability at SPAM Katulampa, Bogor City: Evaluasi Pengendalian Operasional Preventif dalam Menjaga Stabilitas Kekeruhan Air Hasil pada SPAM Katulampa Kota Bogor - Niesa Hanum Mistoro; Enry Adiarto Guntoro; Noviani Ima Wantoputri; Makmur Gunawan; Muhammad Yacob (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Treated water turbidity stability is an important indicator of operational reliability in surface-water-based drinking water treatment plants. This study evaluated preventive operational control at SPAM Katulampa, Bogor City, using daily operational data from 10 February to 10 March 2026 and field observations. The evaluated parameters included raw and treated water turbidity, raw water flow rate, turbidity removal efficiency, and preventive control practices in each treatment unit. Data were analyzed using descriptive statistics and the coefficient of variation, followed by development of a preventive operational control matrix. Raw water turbidity fluctuated markedly, with an average of 58.83 NTU, a range of 12.00–262.98 NTU, and a coefficient of variation of 88.49%. In contrast, treated water turbidity remained stable, averaging 0.61 NTU with a range of 0.52–0.91 NTU and a coefficient of variation of 16.83%, consistently meeting the 3 NTU drinking water standard. Stability was supported by integrated controls at the intake, coagulation, flocculation, sedimentation, filtration, reservoir, and overall operation stages. Key measures included screening, coagulation control, sludge draining, filter backwashing, media maintenance, and final water quality verification. The findings confirm that stable treated water quality results from coordinated preventive control across the treatment train.